Evaluation of the level of techno-agricultural mechanization in six municipalities of the Toluca Valley - Hernández Ávila, Jesús; Gutiérrez Rodríguez, Francisco; Díaz Viquez, Antonio; González Huerta, Andrés; Serrato Cuevas, Rodolfo (Revista Mexicana de Ciencias Agrícolas, 2022)
The fundamental objectives of this research were to know the technical state of the park of tractors and agricultural machines, as well as to analyze the technical-economic indices of this park in the six municipalities of the State of Mexico. It was hypothesized that some mechanization indices were similar to or higher than those shown by FAO. To carry out the present work, non-experimental descriptive studies were carried out, since their purpose was to know the current situation of the functionality of agricultural machines, in six municipalities of the State of Mexico (Zinacantepec, Toluca, Metepec, Almoloya de Juárez, Rayón and Calimaya). According to the analysis and evaluation of these results, no tractor exceeds 450 moto-hours of work per year, in addition, the tractor-area ratio in the municipality of Almoloya de Juárez is 12.81 ha tractor-1, being the highest, and the lowest of 4.44 ha tractor-1 in Toluca-Metepec and what is proposed by FAO is 50 ha tractor-1, which shows the degree of underutilization. The implement-tractor ratio is considered optimal, since the lowest for primary soil preparation implements is 0.98 in Toluca-Metepec and the ratio of the other municipalities is greater than 1. Regarding the age of use of tractors, 46% of these were purchased in the period from 2007 to 2017 and 11.2% are Ford tractors, which have an average of 20 years of use, being considered an obsolete farm machinery park.